Chornobyl: the medical consequenses - legacy 40 years after the accident - Sushko, V.O.; Kolosynska, O.O.; Vdovenko, V.Yu. (Environment & Health, 2026)
Introduction. Nearly 40 years after the Chernobyl Catastrophe, its health effects remain significant for health of the population of Ukraine. Most affected groups include clean-up workers, evacuees, and residents of the radioactively contaminated territories.The aim. To systematize current data on cancer and non-cancer morbidity, mortality, disability, and dose-related factors in the main exposed cohorts; and to define health priorities ahead of the 40th anniversary of the accident.Materials and Methods. Sources include data from the State Registry of Chornobyl victims, long-term epidemiological studies, radiation and hygiene monitoring and dosimetric passportization of settlements. Main indicators: standardized incidence ratios (SIR), excess relative risk (ERR/Gy), mortality structure, and multimorbidity prevalence.Results. Clean-up workers have been found to have an increased cancer incidence (SIR>1), in particular thyroid cancer and leukemia (ERR/Gr>0). The dominance of non-oncological pathology of the cardiovascular, cerebrovascular, endocrine, and respiratory systems has been determined. Increased mortality of victims since the late 1990s and an increase in multimorbidity have been recorded. Current exposure is formed mainly due to the internal accumulation of 137Cs. The full-scale war of 2022 has complicated access to medical care.Conclusions. The high level of cancer morbidity and mortality among victims remains, the main causes of mortality remain cardiovascular and cerebrovascular diseases, and comorbidity plays an important role. Radiation and non-radiation factors of the Chernobyl disaster have a persistent negative impact on health. It is necessary to restore dosimetric control, registry surveillance and international cooperation for effective monitoring and prevention of radiological and medical consequences.
Keywords: Chornobyl; radiation exposure; dosimetric monitoring; cancer morbidity; multimorbidity; clean-up workers; 137Cs